Heat stress in the urban and suburban landscape and its spatial differentiation through the example of a medium-sized city - Vysoudil, Miroslav (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2016)
The spatial distribution of heat stress in a Central European city and its surroundings was examined. We evaluated the length of time for which the threshold values of Humidex and air temperatures were exceeded at individual stations. The longest interval of temperature discomfort was detected at the border of open mid-rise development and open spaces. The shortest intervals were found in compact mid-rise development and near a forest. There are spatial differences between locations with long periods of high temperatures and locations with long intervals of high Humidex values. However, when the heat stress is being assessed in relation to the mortality rate, Humidex does not show better results than the air temperature.
Keywords: Czech Republic; Češka; mesta; microclimate; mikroklima; Olomouc; temperatura; urbana geografija